MiR-590-3p suppresses hepatocellular carcinoma growth by targeting TEAD1 - Xin Ge; Liansheng Gong (Tumor Biology)
MicroRNA signature is altered in different disease states including cancer, and some microRNAs act as oncogenes or tumor suppressors. MiR-590-3p has been shown to be involved in human cancer progression. However, its role in hepatocellular carcinoma remains unknown. In this study, miR-590-3p level was measured, and clinicopathological features were determined in hepatocellular carcinoma tissues. The function of miR-590-3p was examined in vitro and in vivo. Real-time reverse transcription polymerase chain reaction analysis demonstrated downregulation of miR-590-3p in hepatocellular carcinoma tissues, and its downregulation was associated with a poor overall survival of hepatocellular carcinoma patients. Ectopic expression of miR-590-3p promoted growth of hepatocellular carcinoma cells, whereas its depletion inhibited cell growth. Transcriptional enhancer activator domain 1 was identified as a validated miR-590-3p target. Upregulation of transcriptional enhancer activator domain 1 was found in hepatocellular carcinoma tissues and inversely correlated with miR-590-3p. Our results indicate a tumor suppressor role of miR-590-3p in hepatocellular carcinoma through targeting transcriptional enhancer activator domain 1 and suggest its use in the diagnosis and prognosis of liver cancer.